Effects of Nordic walking in Alzheimer’s disease: A single-blind randomized controlled clinical trial - A. Angiolillo; D. Leccese; S. Ciccotelli; G. Di Cesare; K. D'Elia; N. Aurisano; C. Matrone; C. Dentizzi; A. Di Costanzo (Heliyon, 2023)
Non-pharmacological approaches, including exercise programs, have been proposed to improve cognitive function and behavioral symptoms, such as depression, agitation, or aggression, in the management of patients with Alzheimer's disease (AD). Indeed, physical inactivity is one of the main modifiable risk factors in patients with AD, as well as in the development of cardiovascular diseases and related pathologies.Although Nordic Walking (NW), a particular type of aerobic exercise, is known to benefit the health of aging populations, there is little evidence that patients with AD may benefit from this non-pharmacological treatment. In this context, we performed a pilot study in 30 patients with mild/moderate AD to evaluate whether NW influences different cognitive domains, including executive functions, visual-spatial abilities, and verbal episodic memory. To this aim, 15 patients (Control group, CG) underwent reality orientation therapy, music therapy, motor, proprioceptive and postural rehabilitation, and 15 patients (experimental group, EG) in addition to the activities performed by the CG also had the NW with a frequency of twice a week. Neuropsychological assessments and evaluations of daily activities and quality of life were performed at baseline and after 24 weeks. Twenty-two patients, including 13 in the CG and nine in the EG completed the activity program after 24 weeks. The EG showed a significant improvement in the Frontal Assessment Battery, Rey's auditory Verbal Learning Test Delayed Recall, Raven's Colored Progressive Matrices, and completion time for the Stroop Word-Color Interference test, compared to the CG. NW was able to improve cognitive domains like visual-spatial reasoning abilities, verbal episodic memory, selective attention, and processing speed in AD patients. These results, if confirmed by further studies with a larger number of patients and a longer training period, may prospect NW as a safe and likely useful strategy to slow down cognitive impairment in mild/moderate AD.